Doxorubicin has a synergistic cytotoxicity with cucurbitacin B in anaplastic thyroid carcinoma cells - Si Hyoung Kim; Jun Goo Kang; Chul Sik Kim; Sung-Hee Ihm; Moon Gi Choi; Hyung Joon Yoo; Seong Jin Lee (Tumor Biology)
In this study, the combined effect of doxorubicin with cucurbitacin B on survival of anaplastic thyroid carcinoma cells was evaluated. For experiments, 8505C and CAL62 human anaplastic thyroid carcinoma cells were used. Cell viability, the percentage of viable cells, and cytotoxic activity were measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, multiplexed cytotoxicity assay, and cytotoxicity assay, respectively. Reactive oxygen species production was measured. In experiments, doxorubicin and cucurbitacin B reduced cell viability in a dose- and time-dependent manner. Cotreatment of doxorubicin and cucurbitacin B, compared with treatment of doxorubicin alone, decreased the percentage of viable cells and increased cytotoxic activity. All of the combination index values were lower than 1.0, suggesting the synergism between doxorubicin and cucurbitacin B in induction of cytotoxicity. In cells treated with both doxorubicin and cucurbitacin B, compared with doxorubicin alone, the protein levels of cleaved poly(adenosine diphosphate-ribose) polymerase and cyclooxygenase 2 and reactive oxygen species production were enhanced. In contrast, the protein levels of B-cell chronic lymphocytic leukemia/lymphoma 2 and survivin and B-cell chronic lymphocytic leukemia/lymphoma 2/B-cell chronic lymphocytic leukemia/lymphoma 2–associated x protein ratio were diminished. The protein levels of Janus kinase 2 and signal transducer and activator of transcription 3 were reduced, while phospho-extracellular signal–regulated kinase 1/2 protein levels were elevated without change in total extracellular signal–regulated kinase 1/2 protein levels. These results suggest that doxorubicin synergizes with cucurbitacin B in induction of cytotoxicity in anaplastic thyroid carcinoma cells. Moreover, synergistic cytotoxicity of doxorubicin with cucurbitacin B is mediated by B-cell chronic lymphocytic leukemia/lymphoma 2 family proteins, survivin, and reactive oxygen species and modulated by Janus kinase 2/signal transducer and activator of transcription 3 and extracellular signal-regulated kinase 1/2 in anaplastic thyroid carcinoma cells.